Quality of life in overweight and obese children - М.Л. Аряєв; Д.С. Селімханова; І.М. Шевченко (Zdorovʹe Rebenka)
Background. The prevalence of childhood obesity has reached concerning levels worldwide, posing a pressing and serious public health issue. The objective of this study is to examine the quality of life (QoL) in children with elevated body weight and obesity. Materials and methods. The study involved 151 children (71 girls and 80 boys) aged 12 to 17 years. The assessment included measurements of body weight, height, and calculation of body mass index, adjusted for age and sex. Based on body mass index, the children were categorised into three groups: 1 — normal weight; 2 — overweight; 3 — obese. The quality of life of participants was evaluated using the PedsQL™ 4.0 questionnaire. Results. The findings reveal a marked reduction in QoL among obese children, with the extent of QoL decline correlating with the degree of excess weight. The overall QoL score, based on the children’s self-assessment, was significantly lower in higher body weight categories: obesity — 55.96 ± 0.59 points; overweight — 78.97 ± 1.08 points; control group — 84.42 ± 1.69 points. Children in the obesity group reported the greatest reduction in the physical functioning scale, scoring an average of 54.40 ± 3.56 points. In questionnaires completed by parents, the overall QoL scores were as follows: obesity — 56.60 ± 0.77 points; overweight — 79.97 ± 1.11 points; control group — 85.22 ± 2.15 points. Parents identified the largest QoL reduction in the social functioning scale for children with obesity (54.28 ± 2.65 points). Conclusions. The study highlights a direct relationship between increased body weight and reduced QoL. Children’s self-reports indicate the most significant decline in physical functioning, while parents noted a substantial drop in social functioning of children with obesity.